Objectively measured physical activity and sedentary time in children with overweight, obesity and morbid obesity: a cross-sectional analysis - Gabrielle ten Velde; Guy Plasqui; Elke Dorenbos; Bjorn Winkens; Anita Vreugdenhil (BMC Public Health, 2021)
Abstract Background Limited physical activity (PA) and a high level of sedentary time (ST) are associated with childhood obesity and are a target for intervention. This study aimed to assess objectively measured PA and ST in Dutch children across weight categories, age groups and sex. Methods 202 children with overweight, obesity and morbid obesity (55% girls, 12 ± 3y of age, BMI z-score + 3.15 ± 0.73), referred to the Centre for Overweight Adolescents and Children’s Healthcare (COACH, Maastricht UMC+) were included. PA (total PA, light PA and moderate to vigorous PA (MVPA)) and ST were measured with the GT3X Actigraph accelerometer. Wear time validation was set to include at least four days, 480 min/day, including one weekend day. Results PA levels in children with morbid obesity were higher compared to children with obesity, also after correction for age and sex (corrected difference (B) 118 counts per minute (cpm), p = .006). ST was lower in children with morbid obesity compared to children with obesity (B − 51 min/day, p = .018). Girls performed significantly less MVPA than boys (B − 11 min/day, p < .001) and for each year increase of age, children performed less PA (B − 46 cpm, p < .001) and ST increased (B 18 min/day, p < .001). Conclusion PA and ST is different in subgroups of children with overweight, obesity and morbid obesity, depending on sex, age and overweight severity. In particular, children with obesity perform less PA and more ST compared to children with morbid obesity. Future research could explore the preferences and needs for PA and ST in children in the different weight categories. Trial registration The trial is registered with Clinicaltrials.gov NCT02091544 at March 19, 2014.